2009
DOI: 10.1051/dst/2009011
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of glycomacropeptide on dental erosion

Abstract: -Throughout the world, the consumption of acidic foods, soft drinks and fruit juices has increased and has been associated with a rise in dental problems such as caries and erosion. The aim of this study was to investigate the protective effect of glycomacropeptide (GMP) against dental erosion and to compare the effect with that of caseinophosphopeptides (CPP). To assess the contribution of the calcium content of these peptides and their protection, calcium-reduced GMP (GMP-ca) and calcium-reduced CPP (CPP-ca)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The majority of research is focused on caseins (mainly the already mentioned casein phosphopeptides), which in a concentration of 0.002% to 0.2% adsorb on the salivary pellicle or directly on the enamel surface and reduce its dissolution in vitro , probably by forming an ion‐diffusion retarding layer . Recently, the anti‐erosive and remineralizing properties of proteose‐peptone and glycomacropeptide, as well as hen egg ovalbumin have been reported. However, the addition of 0.2% ovalbumin reduces the erosive potential of citric acid in vitro to a lesser extent than 0.2% casein …”
Section: Introductionmentioning
confidence: 99%
“…The majority of research is focused on caseins (mainly the already mentioned casein phosphopeptides), which in a concentration of 0.002% to 0.2% adsorb on the salivary pellicle or directly on the enamel surface and reduce its dissolution in vitro , probably by forming an ion‐diffusion retarding layer . Recently, the anti‐erosive and remineralizing properties of proteose‐peptone and glycomacropeptide, as well as hen egg ovalbumin have been reported. However, the addition of 0.2% ovalbumin reduces the erosive potential of citric acid in vitro to a lesser extent than 0.2% casein …”
Section: Introductionmentioning
confidence: 99%
“…It is produced when chymosin cleaves -casein in cheese making [Nejad et al, 2009]. There has been relatively little work looking at GMP in the context of demineralisation/remineralisation.…”
mentioning
confidence: 99%
“…There has been relatively little work looking at GMP in the context of demineralisation/remineralisation. GMP has been compared to CPP in a hydroxyapatite dissolution model and it was concluded that both proteins can inhibit dental erosion when in a low pH environment (pH ranging from 3 to 4.5) [Nejad et al, 2009]. GMP has also been shown to have some remineralising properties in situ [Aimutis, 2004].…”
mentioning
confidence: 99%
“…It may also be suggested that the higher calcium concentration in itself contributed to the effect of the P++ paste. This could be viewed as an indirect effect of the protein addition, as casein is known to bind calcium, but this is likely to be negligible [Nejad et al, 2010].…”
Section: Discussionmentioning
confidence: 99%